Child’s best interests lose out in big parties politics: the case of foreign adoption - Vagoliņa, Žaklīna (My University, 2018)
The thesis aims to answer the question whether the child best interests have been set as the priority in the bans of foreign adoption in case of Russia and Ethiopia or if it has been just a political move from policymakers to gain attention. The thesis will look more detailed into two case studies: The Russia’s ban on U.S. foreign adoption or Dima Yakovlev law, as well as on the Ethiopia’s ban on foreign adoption, because from 1999 to 2016 Russia took second place as the State, which provides their child to international adoption in sum providing 46 112 children for this time period, meanwhile Ethiopia in this statistic took fifth place by providing 15 319 children to adoption to the United States of America.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Family law; Ethiopia; Russia